Storing nonrelativistic nuclei of hydrogen isotopes - Grigor’ev, Yu.N.; Guk, I.S.; Inopin, E.V.; Kononenko, S.G.; Tarasenko, A.S.; Paschenko, A.V. (Вопросы атомной науки и техники, 2000)
The paper shows that in cyclic magnetic systems the particle stopping losses provide the damping of both the betatron and synchrotron oscillations of hydrogen isotope ions in the energy range 20-80 keV/nucl. Parameters of the storage ring magnetic system and the circulating beam are estimated. Some aspects of such a storage ring application are discussed.